Nutrient Profiling of Snack Bars According to Indonesian Healthier Choice Criteria - Astina, Junaida; Goyudianto, Bryan Ashley; Muslimatun, Siti (Jurnal Gizi dan Pangan, 2023)
This study aims to evaluate the nutrient profiling profile of snack bars according to Indonesian healthier choice criteria for healthier choice. Snack bars were purchased and classified into soy-, cereal-, and other -based snack bars. Nutritional information were was compared with the healthier choice criteria. Soy-based snack bars had the highest protein content (20.94±6.12 g/100 g) compared to others-based snack bars (11.21±5.13 g/100 g) and cereal-based snack bars (8.36±3.55 g/100 g) with p<0.001. Others-based snack bars (15.30±5.54 g/100 g) had the highest dietary fiber content compared to soy-based (8.91±2.11 g/100 g) and cereal-based snack bars (7.06±3.26 g/100 g) with p<0.001. Only two snack bars passed the criteria as “healthier choice” while others need to be reformulated to pass the criteria.